Gastrointestinal Mast Cell Tumor in an African Dormouse (Graphiurus sp.) - Chang, Yen-Chi; Chang, Jung-Chin; Chen, Jo-Wen; Wu, Ying-Chen; Chen, Ter-Hsin (Veterinary sciences, 2022)
Mast cell tumors (MCTs) are well-known neoplasms derived from either mucosal or connective tissue mast cells. While well studied in several domestic species, MCTs are rarely documented in rodents. A three-year-old, male African dormouse (Graphiurus sp.) presented with a history of vomiting and anorexia for 3 months. Sonography revealed thickened gastric mucosa and hyperperistalsis. The patient died after receiving symptomatic treatment for 2 months. At necropsy, locally extensive, pale, thickened mucosal foci obscuring the first half of the stomach lumen was noted. Histological examination revealed moderately polymorphic, round, oval to spindle cells with amphophilic cytoplasmic granules infiltrating the mucosa to tunica muscularis, with moderate numbers of eosinophils. The mucosa was severely ulcerated with the proliferation of granulation tissue. The granules in most tumor cells exhibited metachromasia with the toluidine blue stain. Neoplastic cells revealed positive membranous immunoreactivity to KIT. Herein, we report the first case report of MCT in dormouse but also the first gastrointestinal MCT in a rodent species.